Effects of Storage Temperature at the Early Postharvest Stage on the Firmness, Bioactive Substances, and Amino Acid Compositions of Chili Pepper (Capsicum annuum L.) - Yuan Cheng; Chengan Gao; Shaodan Luo; Zhuping Yao; Qingjing Ye; Hongjian Wan; Guozhi Zhou; Chaochao Liu (Metabolites, 2023)
The commercial and nutritional quality of chili peppers deteriorates rapidly after harvest. So far, little is known about the effect of temperature on postharvest chili pepper quality. This study elucidated the effects of two temperatures (20 °C and 30 °C) on chili peppers’ postharvest firmness, flavor, and nutritional attributes. We found that compared to 20 °C, 30 °C escalated the decline in fruit firmness, capsaicin content, and dihydrocapsaicin content, while enhancing the increment in water loss and electrical conductivity, as well as total carotenoids and ascorbic acid content. The contents of most amino acids (AAs) decreased significantly during postharvest storage compared to their initial values, whether stored at 20 °C or 30 °C; however, 30 °C had a more substantial impact than 20 °C. Meanwhile, as for soluble protein and amino acid compositions, the effect of storage temperature was genotype-dependent, as reflected by differential changes in total AA contents, single AA contents, essential AA ratio, delicious AA ratio, etc., under the 20 °C or 30 °C treatments. In conclusion, our findings reveal the influence of temperature on pepper quality, showing that the storage temperature of 20 °C was better for maintaining chili quality than 30 °C from the perspective of overall commercial attributes.